2004
DOI: 10.2214/ajr.182.6.1821451
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Sphincteroplasty and Transpapillary Elimination of Bile Duct Stones:10 Years' Experience

Abstract: Balloon sphincteroplasty and transpapillary elimination of bile duct stones is an effective and safe technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…Percutaneous transhepatic removal of CBD stones is a minimally invasive alternative for surgical treatment. This approach is not commonly used for patients in whom ERCP treatment is not possible and only a few studies have reported the results of this procedure [17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous transhepatic removal of CBD stones is a minimally invasive alternative for surgical treatment. This approach is not commonly used for patients in whom ERCP treatment is not possible and only a few studies have reported the results of this procedure [17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous antegrade expulsion of bile stones into the duodenum over a dilated papilla was initially described by Meranze et al [10], Muchart et al [11], and Gil et al [12] and then reported by others [2,13,14] in large series of patients. This technique is considered to be safe and effective: maintenance of the anatomic integrity and function of the sphincter is desirable, resulting in a great advantage compared with other treatment techniques, such as endoscopic papillotomy or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The sheath can also be used to administer contrast material, prevent air bubbles, and avoid tract injury [2]. The access to the bile duct permits repetition of the expulsion maneuver as many times as necessary, and having the bile duct with external drainage in position for several days reduces the risk for manipulation-induced cholangitis by precluding sphincter spasm and providing an egress route for infected bile [2,14]. The presence of an internal-external biliary catheter after the procedure enables the option of repeated cholangiography, which may be necessary, for example, if the biliary function deteriorates.…”
Section: Discussionmentioning
confidence: 99%
“…Different interventional techniques have been previously reported to perform percutaneous transhepatic removal of bile duct stones by using a Fogarty balloon catheter [Ozcan et al 2012] or occlusion balloon [García-Vila et al 2004].…”
Section: Discussionmentioning
confidence: 99%